Strategi Komunikasi Digital PT Dirgantara Indonesia dalam Krisis Citra dan Reputasi - Neng Aat Sholihat; Ahmad Taufiq Maulana Ramdan (CV. ITTC INDONESIA, 2026)
The rapid, interactive, and wide-reaching development of online media has increased organizational reputational vulnerability, particularly for strategic state-owned enterprises (SOEs). In 2024, PT Dirgantara Indonesia experienced a reputational crisis following online media coverage regarding delays in salary and employee allowance payments, which initially constituted an internal administrative issue but subsequently evolved into a national public agenda through media framing that emphasized labor conflict and employee perspectives, thereby shaping negative public perceptions before the company was able to deliver effective clarification.This study aims to analyze PT Dirgantara Indonesia’s digital crisis communication strategy in maintaining corporate image and reputation amid negative online media coverage by examining media framing, organizational digital communication responses, and issue management practices during the crisis period.This research adopts a qualitative approach with a case study design. Data were collected through in-depth interviews with internal corporate actors directly involved in crisis communication, analysis of national online media coverage, and documentation of the company’s digital communication outputs. Data analysis was conducted using the interactive analysis model of Miles, Huberman, and Saldaña, encompassing data reduction, data display, and conclusion drawing through iterative thematic coding.The findings indicate that online media framing played a dominant role in shaping public perceptions from the early phase of the crisis. The company’s digital communication strategy, characterized by a formal, centralized, and reactive approach, was effective in maintaining information accuracy but less optimal in proactively constructing public narratives. Bureaucratic issue management processes delayed public responses and reinforced media framing dominance, underscoring the importance of rapid, proactive, and dialogic digital communication strategies in managing SOE reputational crises in the digital media era.